2009
DOI: 10.1016/j.tcs.2008.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of discrete transfinite time Turing machine models: Halting times, stabilization times, and Normal Form theorems

Abstract: The authors present empirical distributions for the halting time (measured by the number of iterations to reach a given accuracy) of optimization algorithms applied to two random systems: spin glasses and deep learning. Given an algorithm, which we take to be both the optimization routine and the form of the random landscape, the fluctuations of the halting time follow a distribution that, after centering and scaling, remains unchanged even when the distribution on the landscape is changed. We observe two qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…What makes this plausible is the connection on both sides with Σ 2 reflection. Welch [14], [15] characterized the closure point of regular ITTMs via L ζ , the least initial segment of L with a Σ 2 elementary extension L Σ . So you would expect FITTMs to have a closure point at some sort of super-Σ 2 reflecting ordinal.…”
Section: B Feedback Ittmsmentioning
confidence: 99%
“…What makes this plausible is the connection on both sides with Σ 2 reflection. Welch [14], [15] characterized the closure point of regular ITTMs via L ζ , the least initial segment of L with a Σ 2 elementary extension L Σ . So you would expect FITTMs to have a closure point at some sort of super-Σ 2 reflecting ordinal.…”
Section: B Feedback Ittmsmentioning
confidence: 99%
“…[77], [83]) (i) Any ITTM computation P e (x) which halts, does so by time λ x , the latter being defined as the supremum of the x-writable ordinals; (ii) any computation P e (x) with eventually stable output tape, will stabilize before the time ζ x defined as the supremum of the eventually x-writable ordinals; (iii) moreover ζ x is the least ordinal so that there exists Σ x > ζ x with the property that…”
Section: Basic Propertiesmentioning
confidence: 99%
“…[28] showed that for almost all f , N P f = P f and later [14] showed that for many α P α = N P α ∩ co-N P α including those α that begin a gap in the clockable ordinals. (Such are admissible by [83] Thm. 50).…”
Section: Complexity Of Ittm-computationmentioning
confidence: 99%
“…The answer turns out, thankfully, to be affirmative, (it follows from the λ, ζ, Σ-Theorem below, [Welch (2000)]). We refer the reader not to the original papers, but to [Welch (2009)] for a later but somewhat tidier account of this theorem and the answers to the above three questions.…”
Section: Infinite Time Turing Machines (Ittm)mentioning
confidence: 99%
“…Theorem 1.2. (Normal Form Theorem I [Welch (2004)], [Welch (2009)]) ∀e∃e ∀n ∈ N P e (n) ↓−→ (P e (n) ↓ y where y ∈ 2 N codes a wellordered course-ofcomputation sequence for P e (x) ↓).…”
Section: Infinite Time Turing Machines (Ittm)mentioning
confidence: 99%